Maja Fruit Extracts Inhibit Escherichia coli, Reduce Fly Larvae Population, and Ammonia Emission of Chicken Excreta - Syaefullah, B. L.; Erwanto, Y.; Wihandoyo; Muhlisin; Prasetyo, R. A.; Kurniawati, N.; Fitriyanto, N. A. (Tropical Animal Science Journal, 2020)
The characteristic of chicken excreta has a very potential as a breeding media for flies and is known for causing odorous pollutants (NH3 emission) from undigested protein and the activities of urease microorganisms. This study is focused on extracting Maja fruit, to quantify marmelosin from different fruit conditions using HPLC, and to determine the biological activity for handling the chicken excreta problems. In this study, the Kirby-Bauer Test was used to observe the antibacterial activity of marmelosin, the NH3 trapping method was used to determine ammonia emission, and the larvae population was determined by the Fly-Grill method. Marmelosin contents in MFE from immature, mature, and fermented fruit condition were 108.65 μg/g; 65.83 μg/g, and 23.02 μg/g, respectively. The increasing level of marmelosin addition to 50, 100, 150, and 200 μg/mL caused the higher diameter of inhibition zone against E. coli (p